Neuregulin 1 Controls Glutamate Uptake by Up-regulating Excitatory Amino Acid Carrier 1 (EAAC1) - Yu, Ha-Nul (J Biol Chem, 2015)
Neuregulin 1 (NRG1) is a trophic factor that is thought to have important roles in the regulating brain circuitry. Recent studies suggest that NRG1 regulates synaptic transmission, although the precise mechanisms remain unknown. Here we report that NRG1 influences glutamate uptake by increasing the protein level of excitatory amino acid carrier (EAAC1). Our data indicate that NRG1 induced the up-regulation of EAAC1 in primary cortical neurons with an increase in glutamate uptake. These in vitro results were corroborated in the prefrontal cortex (PFC) of mice given NRG1. The stimulatory effect of NRG1 was blocked by inhibition of the NRG1 receptor ErbB4. The suppressed expression of ErbB4 by siRNA led to a decrease in the expression of EAAC1. In addition, the ablation of ErbB4 in parvalbumin (PV)-positive neurons in PV-ErbB4(−/−) mice suppressed EAAC1 expression. Taken together, our results show that NRG1 signaling through ErbB4 modulates EAAC1. These findings link proposed effectors in schizophrenia: NRG1/ErbB4 signaling perturbation, EAAC1 deficit, and neurotransmission dysfunction.